2016
DOI: 10.1021/acsnano.6b03853
|View full text |Cite
|
Sign up to set email alerts
|

Large Magnetoresistance at Room Temperature in Organic Molecular Tunnel Junctions with Nonmagnetic Electrodes

Abstract: We report room-temperature resistance changes of up to 30% under weak magnetic fields (0.1 T) for molecular tunnel junctions composed of oligophenylene thiol molecules, 1-2 nm in length, sandwiched between gold contacts. The magnetoresistance (MR) is independent of field orientation and the length of the molecule; it appears to be an interface effect. Theoretical analysis suggests that the source of the MR is a two-carrier (two-hole) interaction at the interface, resulting in spin coupling between the tunnelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…10, and we consider it to be the baseline result of our model. However, we also find that a small exchange splitting of the initial state energy levels and a difference in the gfactors of the electrons forming the initial state pairs can result in negative magnetoresistance over certain field ranges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10, and we consider it to be the baseline result of our model. However, we also find that a small exchange splitting of the initial state energy levels and a difference in the gfactors of the electrons forming the initial state pairs can result in negative magnetoresistance over certain field ranges.…”
Section: Discussionmentioning
confidence: 99%
“…10 The transport was shown to be due to non-resonant tunneling by comparing the conductances of molecules of different lengths, and the relative was found to be essentially independent of the length of the molecule and also independent of the direction of the magnetic field.…”
Section: Itroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Frisbie et al. showed that the Au−S tunnel junction played a significant role in determining the magnetoresistance effect of the Au−(oligophenylene thiol)−Au device . To investigate the role of the junction for the present device, we plotted the PDOS contributions of the junction elements; all other atoms of the device and relevant results are depicted in Figure S5 a and b, respectively, in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The built-in electric field induces an additional charge redistribution across the interface, which modifies the surface electronic properties of condensed matter used as the substrate. To date, the effects of SAM formation on the magnetism, 15,16,1922 conductiv-ity, 9,10,18,23,24 and superconductivity 2527 have been reported by several research groups.…”
Section: Introductionmentioning
confidence: 99%